THE IMPACT OF INFORMATION TECHNOLOGY ON EFL TEACHING IN INDONESIA - Rosmaladewi Rosmaladewi; Amirullah Abduh (ELT Worldwide: Journal of English Language Teaching, 2019)
This study observes the impact of information and communication technology (ICT) on English as a foreign language (EFL) teaching in secondary school focuses on the culture of teachers in Indonesia in 2007 - 2012. Through an observation on the ICT program in teaching English in Indonesia and an analysis of the theory of the culture of teaching, it evidences that the application of ICT in teaching EFL has influenced the teachers’ cultures at schools. It confirms that the use of the internet and World Wide Web as well as social media has strengthened the four culture of teaching in Indonesia; either individualism, balkanization, collaborative, or contrive collegiality. It changes the way of teachers plan teaching materials, perform their teaching in class, and the way they interact with other teachers and students. However, some challenges facing ICT in Indonesia should be solved. Through this analysis, conclusion and some recommendation are presented at the end of this report.